Teman Tapi Beracun: Toxic Friendship Di Kalangan Pelajar: Refleksi Fenomenologis Tentang Pola Pembinaan Penyintas Toxic-Friendship - Amala, Khoirima; Saifuddin; Alivi, Justsinta Sindi (Yayasan Amanah Nur Aman, 2025)
The phenomenon of toxic friendship is increasingly prevalent in school environments, particularly among junior high school students who are in the stage of identity exploration. Friendships, which ideally serve as spaces for emotional support, often develop into interactions characterized by pressure, manipulation, and negative behaviors. This study aims to explore the patterns of addressing toxic friendship at SMPT Darul Dakwah, focusing on three aspects: (1) the forms or characteristics of toxic friendship among students, (2) the contributing factors, and (3) the role of Islamic Education (PAI) teachers in managing these issues. Employing a qualitative approach with a phenomenological method, data were collected through observation, in-depth interviews, and documentation involving eighth-grade students, PAI teachers, and guidance counselors (BK teachers). The findings reveal that toxic friendship manifests in forms such as group exclusivity (cliques), social exclusion, verbal bullying, and emotional manipulation. The contributing factors include family parenting patterns, peer group influence, and the intensity of social media use. PAI teachers implement preventive strategies (instilling religious values), curative approaches (Islamic counseling), and rehabilitative efforts (fostering respect and positive cooperation). These findings highlight the strategic role of PAI teachers in cultivating healthy peer relationships and recommend stronger collaboration with guidance counselors and the school to prevent and address toxic friendship.